ДЕЯКІ ПИТАННЯ БЕЗГОТІВКОВИХ РОЗРАХУНКІВ І ШЛЯХИ ЇХ ВИРІШЕННЯ - Khailova, T.V.; Kuvshynchikova, A.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2014)
The paper explores the economic essence of the category of clearing settlements and determines their role in the modern economy of Ukraine. The advantages and disadvantages of a clearing form of settlements are analyzed, and the ways to improve them are offered. REFERENCES: